PERANCANGAN SISTEM INFORMASI AKUNTANSI PERHITUNGAN PAJAK PPh PASAL 21 PEGAWAI DI KECAMATAN BANDUNG KIDUL KOTA BANDUNG - Viqry Reyfangga Praditama; Hani Hatimatunnisani; Ardi Taryanto (INFOKOM (Informatika & Komputer), 2019)
This research aimed to design of accounting information system calculation income tax article 21employees in Bandung Kidul Sub District Bandung. The method used in designing this information system is the waterfall method. Data collection techniques used were interviews, observation and literature study. From observation that has been done, the factors that inhibited the process of calculation income tax was that they were using Microsoft Office Excel and it was less effective and efficient so need that relative long time in process of calculating income tax. Accordingly, need calculation income tax article 21employees information system that approach with Microsoft Visual Studio 2010 and Microsoft Access 2013 as processing database. With this application as processing the calculation of income tax, it is expected that the data processing can be more optimal.